Towards a concept of Anthropology from a complex approach - Gómez García, Pedro (Pensamiento. Revista de Investigación e Información Filosófica, 2015)
Knowledge of human reality has made great advances through specialized scientific disciplines, such as genetics, sociobiology, evolutionary psychology, and neuroscience. However, it has hardly advanced at all in the so-called social and human sciences, or in philosophical anthropology. In any case, anthropological knowledge is in a state of dispersion, with partial and reductionist approaches. The relatively recent development of theories of complexity offers an epistemological orientation that reveals the inadequacies of the simplified or biased positions, to adopt the general framework of a systematic and evolutionary approach, to build connections between different levels of observation, and to construct models that are sensitive to the multidimensionality of the corresponding reality. The paper proposes an exploration of this latter line of investigation.
Keywords: anthropological theory; reductionism; complex system; emergentism; human evolution; human reality; information